Thermodynamic properties of solutions of ethacrylic acid in acetonitrile and acetic acid - Serheyev, Valentyn; Kos, Yuriy; Van-Chin-Syan, Yuriy (Publishing House of Lviv Polytechnic National University, 2015)
The saturated vapor pressure of ethacrylic acid solutions in acetonitrile and acetic acid was measured by a static tensimetric method in the temperature range of 295–355 K. The composition of the equilibrium phases as well as the activity coefficients were received from the experimental measurements of the temperature-dependent saturated vapor pressure. We then used the temperature and concentration dependent activity coefficients to calculate the excess thermodynamic functions of the solutions mixing (He, Ge, Se). Статичним тензиметричним методом виміряно тиск насиченої пари над розчинами етакрилової кислоти в ацетонітрилі та оцтовій кислоті в температурному інтервалі 295–355 К. За даними температурної залежності тиску насиченої пари розраховано склад рівноважних фаз та коефіцієнти активності компонентів. За температурною та концентраційною залежністю коефіцієнтів активності розраховані надлишкові термодинамічні функції змішування досліджених розчинів (He, Ge, Se).
Термодинамічні властивості розчинів етакрилової кислоти в ацетонітрилі та оцтовій кислоті
Keywords: ethacrylic acid; saturated vapor pressure; activity coefficients; vapor-liquid equilibrium; excess thermodynamic functions; етакрилова кислота; тиск насиченої пари; коефіцієнти активності; рівновага рідина–пара; надлишкові термодинамічні функції